2015
DOI: 10.1038/srep18330
|View full text |Cite
|
Sign up to set email alerts
|

Global insights into acetic acid resistance mechanisms and genetic stability of Acetobacter pasteurianus strains by comparative genomics

Abstract: Acetobacter pasteurianus (Ap) CICC 20001 and CGMCC 1.41 are two acetic acid bacteria strains that, because of their strong abilities to produce and tolerate high concentrations of acetic acid, have been widely used to brew vinegar in China. To globally understand the fermentation characteristics, acid-tolerant mechanisms and genetic stabilities, their genomes were sequenced. Genomic comparisons with 9 other sequenced Ap strains revealed that their chromosomes were evolutionarily conserved, whereas the plasmids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 63 publications
(78 reference statements)
0
27
2
Order By: Relevance
“…The results showed that A. pasteurianus NBRC 101655, A. pasteurianus 386B, and eight A. pasteurianus IFO strains were quite similar with respect to genome structure in the chromosome (Figure 1), which was inconsistent with previous reports (Illeghems et al, 2013; Wang et al, 2015). Moreover, rearrangements, deletions, amplifications, and insertions occurred frequently in A. pasteurianus Ab3, A. pasteurianus subsp.…”
Section: Interpretation Of Data Setcontrasting
confidence: 87%
“…The results showed that A. pasteurianus NBRC 101655, A. pasteurianus 386B, and eight A. pasteurianus IFO strains were quite similar with respect to genome structure in the chromosome (Figure 1), which was inconsistent with previous reports (Illeghems et al, 2013; Wang et al, 2015). Moreover, rearrangements, deletions, amplifications, and insertions occurred frequently in A. pasteurianus Ab3, A. pasteurianus subsp.…”
Section: Interpretation Of Data Setcontrasting
confidence: 87%
“…Arginine decarboxylases have previously been associated with maintenance of bacterial pH homeostasis during acid stress 33 , 34 , which would likely occur during fermentative metabolism. Similarly, both spermidine and putrescine have been associated with acid stress 35 , 36 . A schematic overview of spermine formation by the arginine metabolism, with the related shifts in protein abundance from Xanthomonas , is presented in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the K. hansenii clade again showed to be clearly separated from all the rest of the analyzed strains with the smallest number of toxin–antitoxin systems and unique presence of CRISPR‐Cas system. The importance of the CRISPR‐Cas system in maintaining genome stability in other AAB representatives, Acetobacter pasteurianus CICC 20001 and CGMCC 1.41 strains and their derivatives, was proved recently (Wang, Shao, Chen, Chen, & Chen, ), but no such studies have been done for the Komagataeibacter genus so far.…”
Section: Resultsmentioning
confidence: 99%